Tunupa en Marcapata: las andanzas de San Francisco de Asís y su acólito Phuyutarki en el sur peruano - Pablo F. Sendón (Journal de la Société des Américanistes)
This paper presents and discusses four versions of a myth recorded in the district of Marcapata (Quispicanchi, Cuzco, Peru). The narrative tells the adventures of Patron St. Francis of Assisi and the builder of its church, the hero Phuyutarki. The paper also examines analogies between this myth and some similar texts recorded in the 16th and 17th century sources, and highlights the temporal depth of the relationships among their constitutive elements.